Independent validation of stromal uPA in ABCSG-08: Level 1b evidence for the prognostic value of uPA immunohistochemistry. (August 2022) - Singer, C.F.; Jahn, S.W.; Rudas, M.; Bago-Horvath, Z.; Fitzal, F.; Abete, L.; Moinfar, F.; Gnant, M.; Filipits, M.; ,; Gnant, M.
Abstract: Purpose: To validate the prognostic role of urokinase-type plasminogen-activator (uPA) and plasminogen activator inhibitor type-1 (PAI-1) protein expression in FFPE archived tumor samples when assessed by immunohistochemistry. Patients and methods: Fresh-frozen, paraffin-embedded (FFPE) samples from 303 postmenopausal women with hormone receptor-positive, early breast cancer were investigated. The patients had received 5 years of endocrine therapy in the prospectively randomized ABCSG-8 trial. Immunohistochemistry for stromal uPA and PAI-1 protein expression was correlated with distant recurrence-free survival (DRFS) and overall survival (OS). Results: We detected stromal uPA in 132 of 297 tumors (44.4%) and stromal PAI-1 expression in 74 out of 299 samples (24.7%). Co-expression of uPA and PAI-1 was present in 48 of 294 (16.3%) cases. Neither uPA nor PAI-1 expression was associated with tumor size, age, nodal status, grading, or quantitative receptor status. Patients whose tumor stroma expressed uPA protein had a significantly shorter DRFS (adjusted HR for relapse: 2.78; 95% CI 1.31–5.93; p = 0.008 Cox regression analysis) than women without uPA expression. No such association was seen for PAI-1 and the uPA/PAI1 ratio. After a median follow-up of 5.6 years, women with uPA-positive tumors demonstrated significantly shorter DRFS (93.3% vs. 84.8%; p < 0.013 log-rank test), and tended to have a worse OS (83.0% vs. 77.3%; p = 0.106) compared to women with uPA negative tumors. Conclusion: This independent validation in archived tumor samples from a large prospective randomized trial confirms the clinical utility of stromal uPA evaluation by immunohistochemistry. This provides level 1b evidence for the prognostic role of stromal uPA in women with endocrine-responsive early breast cancer. Highlights: Prospective trial provides level 1b evidence. UPA expression associated with better DDFS and OS.